2002
DOI: 10.1016/s0378-1097(02)00631-6
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylase activity involved in methyl ketone production by Staphylococcus carnosus 833, a strain used in sausage fermentation

Abstract: Staphylococcus carnosus strain 833, inoculated into sausage, increased the levels of methyl ketones which contributed to the cured aroma. These ketones were predicted to arise from incomplete L-oxidation followed by a decarboxylation. To check this hypothesis, we measured the L-decarboxylase activity in resting cells of S. carnosus grown in complex or in synthetic medium, using as substrate a L-ketoacid, which can be an intermediate of the L-oxidation pathway. This activity was present throughout the growth pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…2001). Staphylococcus carnosus was shown to be able to produce methyl ketones from an incomplete β ‐oxidation of fatty acids (Fadda et al. 2002).…”
Section: Introductionmentioning
confidence: 99%
“…2001). Staphylococcus carnosus was shown to be able to produce methyl ketones from an incomplete β ‐oxidation of fatty acids (Fadda et al. 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning S. carnosus , Engelvin et al [3] have reported the existence of a β‐oxidative pathway and the liberation of intermediates from a β‐oxidation cycle. Recently, we have reported a β‐decarboxylase activity in resting cells of S. carnosus using a β‐ketoacid as substrate [4,5]. These results show that S. carnosus , as do fungi, may produce ketones via this pathway.…”
Section: Introductionmentioning
confidence: 68%
“…Since a β‐decarboxylase activity involved in methyl ketone formation was detected for the first time in resting cells of S. carnosus [5], the objective of this work was to characterize the β‐decarboxylase activities present in cell‐free extract (CFE) of S. carnosus 833 strain. The optimal conditions for enzyme activities such as temperature, pH, influence of potential cofactors and/or inhibitors, effect of technological conditions and different substrate affinities were studied.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional use of these food grade staphylococci has been as starter cultures in the ripening process of dry sausages (Liepe, 1982), and strains of S. carnosus have been isolated from fermented meat products throughout the world (Hammes et al, 1995;Fadda et al, 2002). Both strains are characterized as nonsporulating, nonmotile cocci, and grow predominantly in pairs or singly (Schleifer and Kloos, 1975;Schleifer and Fischer, 1982).…”
Section: Staphylococcal Surface Display and Its Applicationsmentioning
confidence: 99%